Shaping global health security through multilateral leadership: A qualitative analysis of Indonesia’s G20 Presidency in 2022 - Dicky Budiman; Heru Subaris Kasjono; Cordia Chu (Poltekkes Kemenkes Yogyakarta, 2026)
Global health security has become a central issue in international governance due to recurrent pandemics and transnational health threats, while the role of multilateral forums such as the Group of Twenty (G20) in reforming global health architecture remains contested. This study aims to examine how Indonesia leveraged its 2022 G20 presidency to shape global health security and contribute to the reform of global health architecture. Using a qualitative research design, this study employed thematic analysis of primary and secondary data. Primary data were obtained from expert interviews and participatory observation related to G20 health processes, while secondary data consisted of official G20 documents, policy reports, and peer-reviewed literature. The data were analysed inductively to identify key themes. The findings show that the G20 serves as a strategic agenda-setting platform for global health security because of its economic and political influence. However, the current global health multilateral system remains fragmented, under-resourced, and weakly coordinated. Indonesia’s presidency promoted strategic initiatives, including strengthening the World Health Organization’s leadership, advancing pandemic preparedness financing, promoting universal health coverage, and addressing health inequities. The study concludes that middle-income countries can shape global health security through sustained multilateral engagement, institutional coordination, and alignment between global commitments and national implementation.